Firm Value and its Non - Linear Relationship with Endogenous Promoter Ownership in India - Satish, D.; Satyanarayana, S. V. (Indian Journal of Finance, 2018)
In India, promoters own a significant portion of the shares of the listed firms. The investors also swear by the names of the promoters behind the firms. In this context, the paper studied the relationship between promoter ownership and firm performance among NSE listed companies by first testing for endogeneity of the promoter ownership variable. The paper also studied the impact of deferential promoters’ holding on performance of these firms. The paper used 2SLS model to study the relationship while taking Tobin Q as a proxy for firm performance. The results showed the existence of a strong relationship between promoter ownership and firm performance, while the non linear study showed a slight U shaped relationship,Â indicating a slight reduction in performance of the firm to a certain pointÂ with an increase in promoter ownership and then a gradual increase in firm performance with an increase in promoter ownership after that point. The results of the non linear study were significant as it showed that the performance of the firms was maximum when the promoter holding in the firms was the highest. This goes against the theory of promoter entrenchment and justifies the craze of Indian investors for promoter led firms with substantial holdings. The research also recommended regulators not to further reduce the maximum promoter holdings which was brought down to 75% for private listed firms in the year 2013 by SEBI.